EFEKTIVITAS METODE TUTOR SEBAYA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN DI SMP YP PGRI DISAMAKAN MAKASSAR - Insani, Nur; Mustamin; Wahab, Abdul; Syahid, Akhmad; Azhar, Muh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the effectiveness of the peer tutoring method in improving the Quran reading skills of Grade VII.1 students at SMP YP PGRI Disamakan Makassar. The research aims to: (1) determine the effectiveness of the peer tutoring method in enhancing students' Quran reading skills; (2) describe the implementation of instruction using the peer tutoring method; and (3) identify the facilitating and inhibiting factors in applying the peer tutoring method to improve students' Quran reading skills. The study employs a mixed-methods approach with an explanatory sequential design, involving the collection and analysis of quantitative data followed by qualitative data. The research subjects consisted of 32 Grade VII.1 students and one Islamic Religious Education teacher. Data collection techniques included tests, interviews, observations, and documentation. Quantitative data were analyzed using the N-Gain test, while qualitative data were analyzed descriptively. The results indicate that the application of the peer tutoring method can improve students' Quran reading skills. This is evidenced by the increase in the average score from 73.03 in the pretest to 84.12 in the posttest. The N-Gain test yielded an average score of 0.43 (or 43.43%), falling into the "medium" category and indicating that the peer tutoring method is reasonably effective. Thus, the peer tutoring method has a positive impact on improving students' Quran reading skills and can serve as an effective alternative teaching method to support the enhancement of Quran reading proficiency in schools.